The response mechanism of the HVA1 gene in hulless barley under drought stress - Yao, Xiaohua; Wu, Kunlun; Yao, Youhua; Li, Jie; Ren, Youcheng; Chi, Dezhao (Italian Journal of Agronomy, 2017)
HVA1, a member of LEA3 (late embryogenesis abundant protein, group 3), is closely related to water stress. However, the response of HVA1 to drought remains unknown in hulless barley. In this study, cultivars with high (Handizi), intermediate (Kunlun 12), and low (Dama) drought tolerance were selected from 28 hulless barley cultivars from the Tibet-Qinghai plateau to explore the drought response mechanism of HVA1. Then, HVA1 was cloned and the expression of the three cultivars was studied using exposure to polyethylene glycol (PEG) 6000. HVA1s in the three hulless barleys were highly homologous at the nucleotide and amino acid levels with over 99% identity. Real-time quantitative polymerase chain reaction showed that the expression level of HVA1 induced by PEG 6000 had a single peak curve in the three cultivars, but higher HVA1 transcript accumulation was seen in Handizi than in Kunlun 12 and Dama under the same drought stress. This result was also proved in eight hulless barleys. The expression level was a better predictor of drought resistance than the genetic structure of HVA1.